Pro Oracle Application Express - Scott, John; Spendolini, Scott (Apress : Imprint: Apress, 2008)
Application Express, or APEX, is one of the most innovative products to come out of Oracle in years. APEX is an application development framework for developing database-backed applications. It's easy enough to get started in that power users can quit storing data in random spreadsheets and instead centralize their data in the powerful Oracle database, all without developer help. Developers aren't left out, however. Those who choose to do so can go deep and leverage the full power and flexibility of Oracle's database engine. Getting started with APEX is easy; learning how to take full advantage of APEX is the problem. It was the problem, that is, until this book came along. In Pro Oracle Application Express, authors John Scott and Scott Spendolini open the "hood" of APEX and expose the full power behind its easy-to-use GUI. They show you what you need to know to produce powerful, professionally polished applications-such as user-authentication models, approaches to layout and navigation, how to integrate Ajax, how to deal with localization issues such as time zones and translations, how to customize the look and feel of an APEX web site, and much, much more. The authors are well-qualified to write on APEX. John Scott runs ShellPrompt, a hosting service that handles many large-scale APEX applications, some of which he is paid to develop. John is a hard-core APEX developer. His co-author, Scott Spendolini, is one of the original creators of APEX. Both John and Scott now base their full-time careers on developing APEX applications. Pro Oracle Application Express is your opportunity to learn APEX from the very best.